relation, listening, writing HUBUNGAN KEMAMPUAN MENYIMAK CERPEN DENGAN KETERAMPILAN MENULIS CERPEN SISWA KELAS XI MAN LUBUK ALUNG: HUBUNGAN KEMAMPUAN MENYIMAK CERPEN DENGAN KETERAMPILAN MENULIS CERPEN SISWA KELAS XI MAN LUBUK ALUNG - Dwi Mutia Chan; Desi Ratna Sari (Universitas Muhammadiyah Muara Bungo, 2019)
The research was conducted to analyze first, students comprehension in listening to the short story. Second, Students Comprehension in writing the short story by the eleventh grade of MAN Lubuk Alung. Third, to relate the comprehension of listening and writing by the eleventh grade of MAN Lubuk Alung. The theory of this research were the competency in listening, writing and analyzing the short story. The type of this research was quantitative research with analitycal descriptive method and used a correlational research schema . The population and sample of this research was the eleventh grades of MAN Lubuk Alung. The sample of this research is 30 students. The data collected by objective test and writing test. The objective test used to collect the data about the comprehension of listening a short story. Writing test used to collect the data about comprehension of writing short story. From this research, it can be concluded that first, the comprehension of writing short story by eleventh grade of MAN Lubuk Alung was Significant (87,96), second the comprehension of listening short story by eleventh grade of MAN Lubuk Alung was very good. Third, the relation between listening and writing skill was significant by freedom degree n-1 (30-1+29) and p=0,95. It means, comprehension h0 ignored and h1 accepted, by the result of tcalculate bigger than ttable 7,18>7,10.